Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1021/acscatal.7b02899
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Roles of Electric Fields in Catalysis: A Perspective

Abstract: This Perspective illustrates how the presence of internal and external electric fields can affect catalytic activity and selectivity, with a focus on heterogeneous catalysts. Specifically, experimental investigations of the electric field influence on catalyst selectivity in pulsed field mass desorption microscopes, scanning tunneling microscopes, probe–bed–probe reactors, continuous-circuit reactors, and capacitor reactors are described. Through these examples, we show how the electric field, whether external… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
245
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(259 citation statements)
references
References 181 publications
5
245
0
Order By: Relevance
“…The obtained interfacial fields are on the order of 0.1 V·Å −1 . The electrostatic contribution to the CO-adsorption energy as a function of the local field is (46,113)…”
Section: Resultsmentioning
confidence: 99%
“…The obtained interfacial fields are on the order of 0.1 V·Å −1 . The electrostatic contribution to the CO-adsorption energy as a function of the local field is (46,113)…”
Section: Resultsmentioning
confidence: 99%
“…Up to now, some endeavors had been done to develop a new methodology in accordance with green chemistry principles . An emerging greener catalyst is coming into one's sight, which is the external electric field (EEF), as a smart reagent to catalyze reactions had been reported by theory and experiment . Especially, the experiment of EEF by Aragonés et al paved the way for the development of EEF in catalyzing chemistry reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[52][53][54][55][56] An emerging greener catalyst is coming into one's sight, which is the external electric field (EEF), as a smart reagent to catalyze reactions had been reported by theory and experiment. [57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74] Especially, the experiment [66] of EEF by Aragonés et al paved the way for the development of EEF in catalyzing chemistry reactions. Recently, our group firstly tried to study the effect of EEF on hydroboration, [75,76] and the results demonstrated that EEF could be used in the hydroboration of C C and C N compounds.…”
Section: Introductionmentioning
confidence: 99%
“…With the continuous development of various catalysts on chemical reactions, the field of oriented external electric field (EEF) has led to a considerable progress . This is initially driven by the harness of electric field to achieve the reaction selectivity or obtain a desired mechanism .…”
Section: Introductionmentioning
confidence: 99%
“…With the continuous development of various catalysts on chemical reactions, the field of oriented external electric field (EEF) has led to a considerable progress. [1][2][3][4][5] This is initially driven by the harness of electric field to achieve the reaction selectivity or obtain a desired mechanism. [6][7][8][9] To this extent, the oriented EEF was developed and used in theoretical studies more and more on the bond activations, [10][11][12][13][14][15][16][17] such as the halogen bond [10] and σ-bonds, [11,12] and chemical reactions, [18][19][20][21][22][23][24][25][26][27][28][29][30][31] such as the substitution reactions, [19] Menshutkin reaction, [20] Diels-Alder reaction, [21,22] hydroboration reaction, [23][24][25][26] and Azide-alkyne reactions.…”
Section: Introductionmentioning
confidence: 99%